TAK1 in brain endothelial cells mediates fever and lethargy - Ridder, Dirk; Lang, Ming-Fei; Salinin, Sergei; Röderer, Jan-Peter; Struss, Marcel; Maser-Gluth, Christiane; Schwaninger, Markus (Journal of experimental medicine, 2011)
Systemic inflammation affects the brain, resulting in fever, anorexia, lethargy, and activation of the hypothalamus-pituitary-adrenal axis. How peripheral inflammatory signals reach the brain is still a matter of debate. One possibility is that, in response to inflammatory stimuli, brain endothelial cells in proximity to the thermoregulatory centers produce cyclooxygenase 2 (COX-2) and release prostaglandin E2, causing fever and sickness behavior. We show that expression of the MAP kinase kinase kinase TAK1 in brain endothelial cells is needed for interleukin 1β (IL-1β)-induced COX-2 production. Exploiting the selective expression of the thyroxine transporter Slco1c1 in brain endothelial cells, we generated a mouse line allowing inducible deletion of Tak1 specifically in brain endothelium. Mice lacking the Tak1 gene in brain endothelial cells showed a blunted fever response and reduced lethargy upon intravenous injection of the endogenous pyrogen IL-1β. In conclusion, we demonstrate that TAK1 in brain endothelial cells induces COX-2, most likely by activating p38 MAPK and c-Jun, and is necessary for fever and sickness behavior.